2018
DOI: 10.19173/irrodl.v19i5.3549
|View full text |Cite
|
Sign up to set email alerts
|

Hacking History: Redressing Gender Inequities on Wikipedia Through an Editathon

Abstract: Editathons are a relatively new type of learning event, which enable participants to create or edit Wikipedia content on a particular topic. This paper explores the experiences of nine participants of an editathon at the University of Edinburgh on the topic of the Edinburgh Seven, who were the first women to attend medical school in 19th century United Kingdom. This study draws on the critical approach to learning technology to position and explore an editathon as a learning opportunity to increase participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(19 reference statements)
0
10
0
1
Order By: Relevance
“…Therefore, there is a lower retention rate among women than men, a finding consistent with Lam et al [ 12 ]. Although edit-a-thons oriented toward introducing women to Wikipedia appear to be a good lure [ 28 , 46 – 48 ], these friendly and supportive scenarios need to be more than sporadic events that disappear a few days later [ 19 , 49 ]. Indeed, this is a well-known factor reported by women editors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a lower retention rate among women than men, a finding consistent with Lam et al [ 12 ]. Although edit-a-thons oriented toward introducing women to Wikipedia appear to be a good lure [ 28 , 46 – 48 ], these friendly and supportive scenarios need to be more than sporadic events that disappear a few days later [ 19 , 49 ]. Indeed, this is a well-known factor reported by women editors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research on edit-a-thons, however, view the events with a pedagogical lens considering them as collaborative learning events [7,21,30]. Oliver investigated the use of edit-a-thons as a substitute for classroom assignments when teaching information literacy.…”
Section: Wikipedia Editing and Edit-a-thonsmentioning
confidence: 99%
“…Student's reflections in form of qualitative and quantitative data showed that they learned valuable lessons on researching information and writing, especially how to be critical about information sources [21]. Hood and Littlejohn, via the means of interviews, captured narrative learning stories of nine participants taking part in an edit-a-thon held at the University of Edinburgh [7]. The edit-a-thon was designed as an informal professional learning event that combines online activity with offline, in-person collaboration and interaction.…”
Section: Wikipedia Editing and Edit-a-thonsmentioning
confidence: 99%
See 2 more Smart Citations